173k views
2 votes
3(x-1)-2(2x+1)=8(x-1)

2 Answers

6 votes

3(x-1)-2(2x+1)=8(x-1)

Use distributive property:

3x-3 -4x-2 = 8x-8

Combine like terms:

-x -5 = 8x -8

Add 8 to both sides:

-x +3 = 8x

Add x to both sides:

3 = 9x

Divide both sides by 9:

x = 3/9

x = 1/3

User Walery Strauch
by
5.1k points
6 votes

Answer:

x = 1/3

Explanation:

3(x-1)-2(2x+1)=8(x-1)

Distribute

3x -3 -4x-2 = 8x -8

Combine like terms

-x -5 = 8x -8

Add x to each side

-x-5+x = 8x-8+x

-5 = 9x-8

Add 8 to each side

-5+8 = 9x-8+8

3 = 9x

Divide by 9

3/9 = 9x/8

1/3 =x

User Benishky
by
5.9k points